2019
DOI: 10.1177/2045125319859964
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and safety of deltoid or gluteal injection of aripiprazole lauroxil NanoCrystal® Dispersion used for initiation of the long-acting antipsychotic aripiprazole lauroxil

Abstract: Background: Aripiprazole lauroxil (AL), a long-acting injectable antipsychotic for the treatment of schizophrenia in adults, can be started with either 21 days of daily oral aripiprazole supplementation or a 1-day initiation regimen consisting of a single injection of a NanoCrystal® Dispersion formulation of AL (ALNCD) and a single dose of 30 mg oral aripiprazole. This phase I study assessed the pharmacokinetics and safety of deltoid versus gluteal ALNCD injections. Methods: Patients with schizophrenia or schi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 8 publications
1
10
0
Order By: Relevance
“…Aripiprazole lauroxil (AL) Three randomized studies assessed pharmacokinetic profiles after single injections of AL and two studies applied multiple injections. As described previously, higher peak plasma concentrations were found following administration to the deltoid site when compared with the gluteal site (Hard et al 2019;Schoretsanitis et al 2021).…”
Section: Tdm For Long-acting Injectable (Lai) Aripiprazolesupporting
confidence: 76%
“…Aripiprazole lauroxil (AL) Three randomized studies assessed pharmacokinetic profiles after single injections of AL and two studies applied multiple injections. As described previously, higher peak plasma concentrations were found following administration to the deltoid site when compared with the gluteal site (Hard et al 2019;Schoretsanitis et al 2021).…”
Section: Tdm For Long-acting Injectable (Lai) Aripiprazolesupporting
confidence: 76%
“…32 Aripiprazole containing formulations Table 4 outlines the three different formulations available that contain aripiprazole, with one of them (aripiprazole lauroxil nanocrystal dispersion) reserved for the initiation of aripiprazole lauroxil. 20,[40][41][42][43][44][45][46] Principal differences between the formulations include approved indications, dosage forms/strengths, reconstitution requirements, injection sites, needle gauge/length, injection volume, injection interval, requirement for oral supplementation, concomitant use instructions with CYP3A4 inducers, and instructions for early or late dosing.…”
Section: Risperidone/paliperidone Containing Formulationsmentioning
confidence: 99%
“…Initiation of aripiprazole lauroxil requires either 21 days of supplementation with oral aripiprazole or the use of the aripiprazole lauroxil nanocrystal dispersion (ALNCD) formulation, available since 2018. 41,42,45,46 ALNCD contains nanometer-sized particles instead of the micrometer-sized particles contained in standard aripiprazole lauroxil; the smaller particles have faster dissolution properties when injected into the muscle. 42 An injection of the ALNCD formulation into either the deltoid or gluteal muscle, plus administration of oral aripiprazole 30 mg that same day, can substitute for the 21 days of oral supplementation that would otherwise be required when starting aripiprazole lauroxil.…”
Section: Risperidone/paliperidone Containing Formulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding LAI paliperidone, the effective dose found was 120–150 mg. 62–64 Several studies found higher peak PLs after administration in the deltoid than in the gluteal. 41 , 65 Although some studies showed a correlation between dose and PLs with both ARI and AOM, 58 , 66 , 67 the evidence of a clear relationship between LAI PLs effectiveness and side effects is scarce, 66 , 67 which It does not mean that it does not exist. 68 , 69 In general, it is considered unlikely that high levels of SGA-LAI improve response, but also that they increase adverse effects.…”
Section: Discussionmentioning
confidence: 99%